Acyl-Enzymes as Thrombolytic Agents in Dog Models of Venous Thrombosis and Pulmonary Embolism - Dupe, R J; English, P D; Smith, R A G; Green, J (Thrombosis and Haemostasis, 1984)
A quantitative model of venous thrombosis in the beagle dog is described. The model was adapted to permit ageing of isolated experimental clots in vivo. A model of acute pulmonary embolism in this species is also described. In the venous thrombosis model, infusion of streptokinase (SK) or SK-activated human plasmin gave significant lysis but bolus doses of SK. plasmin complex were ineffective. Active site anisoylated derivatives of SK. plasminogen complex, SK-activated plasmin and activator-free plasmin were all active when given as bolus doses in both models. At lytic doses, the acyl-enzymes caused fewer side-effects attributable to plasminaemia than the corresponding unmodified enzymes.
Keywords: Thrombolysis; Venous thrombosis; Pulmonary embolism; Dogs; Acylated enzymes